2013
DOI: 10.1016/j.jcta.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Subsets of products of finite sets of positive upper density

Abstract: In this note we prove that for every sequence (m q ) q of positive integers and for every real 0 < δ 1 there is a sequence (n q ) q of positive integers such that for every sequence (H q ) q of finite sets such that |H q | = n q for every q ∈ N and for every D ⊆ kthere is a sequence ( J q ) q , where J q ⊆ H q and | J q | = m q for all q, such that k−1 q=0 J q ⊆ D for infinitely many k. This gives us a density version of a well-known Ramsey-theoretic result. We also give some estimates on the sequence (n q ) q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Milliken further proved in [17] that the collection of strong trees forms, in modern terminology, a topological Ramsey space. Further variations and applications include ω many perfect trees in [15]; partitions of products in [2]; the density version in [5]; the dual version in [21]; canonical equivalence relations on finite strong trees in [22]; and applications to colorings of subsets of the rationals in [1] and [23], and to finite Ramsey degrees of the Rado graph in [18] which in turn was applied to show the Rado graph has the rainbow Ramsey property in [4], to name just a few.…”
Section: Introductionmentioning
confidence: 99%
“…Milliken further proved in [17] that the collection of strong trees forms, in modern terminology, a topological Ramsey space. Further variations and applications include ω many perfect trees in [15]; partitions of products in [2]; the density version in [5]; the dual version in [21]; canonical equivalence relations on finite strong trees in [22]; and applications to colorings of subsets of the rationals in [1] and [23], and to finite Ramsey degrees of the Rado graph in [18] which in turn was applied to show the Rado graph has the rainbow Ramsey property in [4], to name just a few.…”
Section: Introductionmentioning
confidence: 99%
“…The second result included in this work consists of an extension of the main theorem of [18], which established a density version of a Ramsey theoretic result proved in [3,17]. In particular, it was shown that, for every positive real ε and every sequence (m q ) q∈N of positive integers, there exists a sequence (n q ) q∈N of positive integers with the following property.…”
Section: Introductionmentioning
confidence: 90%
“…For instance, each I q can be chosen to be an arithmetic or a polynomial progression. The construction of the sequence (I q ) q∈N is effective, avoiding, in particular, compactness arguments as in [18].…”
Section: Introductionmentioning
confidence: 99%
“…An important result regarding partition relations for trees is the Halpern-Läuchli Theorem [5], which concerns partitions of finite products of infinite trees. The Halpern-Läuchli Theorem has produced many variations and generalizations, such as Milliken's theorem [7] on finite partitions of strong trees, countable colorings of perfect trees [6], and a dual version [11]. For a fuller discussion of the theorem and its variants, see [3] and the references therein.…”
Section: Introductionmentioning
confidence: 99%